Analisis Strategi Bisnis Usaha Mikro Kecil Dan Menengah Toko Kue: Studi Kasus Pada Usaha Kue Bolu Ina Boy - Lucky Mahesa Yahya; Vinda Putri Yanda; Dinda Indriyani; Abdul Hafid (AKUNTANSI 45, 2024)
The goal of business analysis of sponge cake companies is to comprehend the variables that affect their competitive market performance. Numerous important factors, including the external and internal environments as well as social and cultural factors, must be taken into account in this analysis. Several analysis techniques, including SWOT, STP, and market analysis, can be applied to business analyses of sponge cake companies. Finding an overview of the application of SWOT, STP, and market analysis in the "Kue Bolu Ina Boy" business is the aim of this study. By using these techniques, sponge cake companies can better understand the opportunities and challenges they face and develop a business plan that will maximize their growth and performance. Through appropriate business analysis, a sponge cake company can maximize productivity and boost earnings. In addition, business analysis can support sponge cake companies in adapting to changing circumstances and staying competitive in a market that is becoming more and more crowded.